Bioethics of intervention in the technological conjuncture of South America.: Datification of the human (Horizontes de Enfermería, 2020)
Faced with the important development of science and technology, contemporary societies have been affected in several ways. For example, progress has been made to improve people’s lifestyle, but inequalities have grown deeply among those who have access to new technology and those who don´t, besides, this last-mentioned has become vulnerable groups for organizations with influences that make use of personal information in an indiscriminately way and without respect of privacy, confidentiality or individual autonomy, pursuing the benefit of only a few ones. New colonialism is now being lived, where that irrational and excessive dependence raises several ethical questions, which becomes into an applied Bioethics (intervention Bioethics), that allows the discovery of alternatives to support the solution of realities such as inequality, discrimination, and abuse; in this work intervention Bioethics, is presented as a tool that protects society from the illegitimate and illegal use of information from organizations that operate with Big data.
Keywords: big data; bioethics; intervention bioethics.